Advantages of a next generation sequencing targeted approach for the molecular diagnosis of retinoblastoma. Issue 1 (December 2015) - Grotta, Simona; D'Elia, Gemma; Scavelli, Rossana; Genovese, Silvia; Surace, Cecilia; Sirleto, Pietro; Cozza, Raffaele; Romanzo, Antonino; De Ioris, Maria; Valente, Paola; Tomaiuolo, Anna; Lepri, Francesca; et al.
Abstract Background Retinoblastoma (RB) is the most common malignant childhood tumor of the eye and results from inactivation of both alleles of theRB1 gene. Nowadays RB genetic diagnosis requires classical chromosome investigations, Multiplex Ligation-dependent Probe Amplification analysis (MLPA) and Sanger sequencing. Nevertheless, these techniques show some limitations. We report our experience on a cohort of RB patients using a combined approach of Next-Generation Sequencing (NGS) andRB1 custom array-Comparative Genomic Hybridization (aCGH). Methods A total of 65 patients with retinoblastoma were studied: 29 cases of bilateral RB and 36 cases of unilateral RB. All patients were previously tested with conventional cytogenetics and MLPA techniques. Fifty-three samples were then analysed using NGS. Eleven cases were analysed byRB1 custom aCGH. One last case was studied only by classic cytogenetics. Finally, it has been tested, in a lab sensitivity assay, the capability of NGS to detect artificial mosaicism series in previously recognized samples prepared at 3 different mosaicism frequencies: 10, 5, 1 %. Results Of the 29 cases of bilateral RB, 28 resulted positive (96.5 %) to the genetic investigation: 22 point mutations and 6 genomic rearrangements (four intragenic and two macrodeletion). A novel germline intragenic duplication, from exon18 to exon 23, was identified in a proband with bilateral RB. Of the 36 available cases of unilateral RB, 8 patients resulted positive (22 %) to the genetic investigation: 3 patients showed point mutations while 5 carried large deletion. Finally, we successfully validated, in a lab sensitivity assay, the capability of NGS to accurately measure level of artificial mosaicism down to 1 %. Conclusions NGS andRB1 -custom aCGH have demonstrated to be an effective combined approach in order to optimize the overall diagnostic procedures of RB. Custom aCGH is able to accurately detect genomic rearrangements allowing the characterization of their extension. NGS is extremely accurate in detecting single nucleotide variants, relatively simple to perform, cost savings and efficient and has confirmed a high sensitivity and accuracy in identifying low levels of artificial mosaicisms.